Clinical Characterization and Treatment Response of Folliculitis Decalvans Lichen Planopilaris Phenotypic Spectrum: A Unicentre Retrospective Series of 31 Patients - Ana Melián-Olivera; Óscar Moreno-Arrones; Patricia Burgos-Blasco; Ángela Hermosa-Gelbard; Pedro Jaén-Olasolo; Sergio Vañó-Galván; David Saceda-Corralo (Medical Journals Sweden, 2024)
Folliculitis decalvans and lichen planopilaris phenotypic spectrum has been described as a form of cicatricial alopecia. The aim of this study is to describe the clinical and trichoscopic features and therapeutic management of this condition in a series of patients. A retrospective observational unicentre study was designed including patients with folliculitis decalvans and lichen planopilaris phenotypic spectrum confirmed with biopsy. A total of 31 patients (20 females) were included. The most common presentation was an isolated plaque of alopecia (61.3%) in the vertex. Trichoscopy revealed hair tufting with perifollicular white scaling in all cases. The duration of the condition was the only factor associated with large plaques (grade III) of alopecia (p = 0.026). The mean time to transition from the classic presentation of folliculitis decalvans to folliculitis decalvans and lichen planopilaris phenotypic spectrum was 5.2 years. The most frequently used treatments were topical steroids (80.6%), intralesional steroids (64.5%) and topical antibiotics (32.3%). Nine clinical relapses were detected after a mean time of 18 months (range 12-23 months). Folliculitis decalvans and lichen planopilaris phenotypic spectrum is an infrequent, but probably underdiagnosed, cicatricial alopecia. Treatment with anti-inflammatory drugs used for lichen planopilaris may be an adequate approach.